Clasificación de alimentos consumidos en tiendas escolares, según contenido de nutrientes trazadores de riesgo, Medellín – 2012 (2014)
ABSTRACT: The aim this study was to establish a classification of the most consumed foods in school stores (snacks, cakes, cookies, candy and sugary drinks) according to the degree of health risk. A cross, by which nutritional components were identified and no nutrient declared in the nutrition label of the foods most consumed by school stores Medellin commercial lot, then your risk is classified according to the number and amount of these components. 38 snacks, 17 sweet 44 cakes, cookies and cereal bars, and sugary drinks 31: A total of 130 products were analysed. We found that severe risk foods have business presentations over 45 g, are foods with artificial flavors and colors, with fillings inside, with chocolates. And Food Without Risk presented opposite the above features, business presentations less than 20g, without artificial flavors and colors, all soft drinks were classified as moderate.